A new species of direct-developing frog of the genus Pristimantis (Anura: Terrarana: Craugastoridae) from Cordillera del Cóndor, Ecuador, with comments on threats to the anuran fauna of the region - Valencia, Jorge H.; Dueñas, Manuel R.; Székely, Paul; Batallas, Diego; Pulluquitín, Francisco; Ron, Santiago R. (Zootaxa, 2017)
A new frog in the genus Pristimantis is described from a cloud forest on the western flanks of the Cordillera del Cóndor and eastern Andean slopes in the province of Zamora Chinchipe, southeastern of Ecuador. We inferred its phylogenetic position using DNA sequences of mitochondrial and nuclear genes. The new species is strongly supported as part of a clade that includes P. ardalonychus, P. cajamarcensis, P. ceuthospilus, P. chalceus, P. minutulus, P. luteolateralis, P. parvillus, P. ockendeni, P. unistrigatus, and P. walkeri. It can be distinguished from all other species from Cordillera del Cóndor and congeneric species by the unique combination of the following characters: (1) iris light blue with black reticulations; (2) skin of dorsum finely shagreen with scattered pustular tubercles and absence of dorsal folds; (3) tympanic membrane and tympanic annulus visible; (4) snout rounded in dorsal and lateral view; (5) upper eyelid bearing two or three enlarged subconical tubercles; (6) cranial crest absent; (7) males lacking vocal sac and slits; and (8) venter uniformly bright red, light red, salmon or orange. The new species is most closely related to P. ardalonychus, P. cajamarcensis, P. ceuthospilus, P. ockendeni and P. unistrigatus. We consider the new species to be Endangered following IUCN criteria because it has been severely affected by large scale open-pit mining in some localities. Currently, the amphibian fauna of the Cordillera del Cóndor and nearby protected areas are threatened by large–scale copper and gold mining projects with devastating effects on ~20 species, including several undescribed ones.